2007
DOI: 10.1111/j.1365-2478.2007.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of fluid distribution using time‐lapse seismic

Abstract: A B S T R A C TAlthough previous seismic monitoring studies have revealed several relationships between seismic responses and changes in reservoir rock properties, the quantitative evaluation of time-lapse seismic data remains a challenge. In most cases of time-lapse seismic analysis, fluid and/or pressure changes are detected qualitatively by changes in amplitude strength, traveltime and/or Poisson's ratio.We present the steps for time-lapse seismic analysis, considering the pressure effect and the saturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Combining multiple physical measurements of different modalities may be a better approach. For example, there are significant uncertainties in the quantitative analysis of only time‐lapse seismic measurements over petroleum reservoirs [ Landrø , 2002; Furtney and Woods , 2006; Tsuneyama and Mavko , 2007]. Yet it is observed that fluid withdrawal from a reservoir may be associated with geomechanical deformations (especially in weak rock formations) and seismic time shifts [e.g., Minkoff et al , 2004; Hatchell and Bourne , 2005; Aarre , 2006; Rickett et al , 2007].…”
Section: Challenges Opportunities and Future Directionsmentioning
confidence: 99%
“…Combining multiple physical measurements of different modalities may be a better approach. For example, there are significant uncertainties in the quantitative analysis of only time‐lapse seismic measurements over petroleum reservoirs [ Landrø , 2002; Furtney and Woods , 2006; Tsuneyama and Mavko , 2007]. Yet it is observed that fluid withdrawal from a reservoir may be associated with geomechanical deformations (especially in weak rock formations) and seismic time shifts [e.g., Minkoff et al , 2004; Hatchell and Bourne , 2005; Aarre , 2006; Rickett et al , 2007].…”
Section: Challenges Opportunities and Future Directionsmentioning
confidence: 99%
“…When producing the hydrocarbons, there are several reservoir properties which undergo changes, such as fluid (water) saturation, pore pressure, thickness and temperature. However, the focus of this study is on the effects of changes in water saturation (Sw) and pore pressure which are dominant in most clastic reservoirs (Fanchi et al 1999;Landrø et al 2003;Tsuneyama and Mavko 2007;Ji 2017) and those expected in J-Area field. The study used two types of data sets; well data and two sets of 3D seismic data.…”
Section: Methodsmentioning
confidence: 99%
“…Time‐lapse studies also provide a means to study geophysical parameters, by analysing their variations over time (water saturation or weathering for example). In geophysics, it can be challenging to monitor water saturation, as demonstrated by numerous publications (Stovas and Landrø ; Kowalsky, Finsterle, and Rubin ; Tsuneyama and Mavko ; Clément et al . ; Jacob et al .…”
Section: Introductionmentioning
confidence: 99%